An analysis of the role of the school in teaching democratic values: A case of three selected primary schools in Shamva district, Zimbabwe - Dzavo, Joseph; Luggyab, Simon K.; Tanga, Magdeline N. (The Dyke, 2022)
The role of schools is critical in the effective teaching of democratic values in learners worldwide. The effective role of the schools should be reflected through the products churned out to the community. This study was necessitated by the continual abuse of democratic values by school leavers in Shamva district before, during and after elections despite the expected role of the schools. Though the study is cognisant of the possibilities of other factors influencing the output of school graduates, the study wonders if schools really teach democratic values as enshrined in the curriculum, basing on the noted behaviour by school leavers. This paper examines the role of primary schools in promoting democratic values of justice, equality and liberty in pupils in Shamva district, Zimbabwe. Using a qualitative approach, the study is located within the interpretivist research paradigm. A case study design was adopted, and three primary schools in the Shamva district were purposefully, and conveniently selected for this study. The study was underpinned by Rogan and Grayson’s theory of curriculum implementation and reconstructionism theories. The findings of the study revealed that schools had challenges in teaching democratic values to learners. Challenges included difficulties in interpreting the syllabi on the teaching of democratic values in learners; community challenges regarding democratic values viewed as sensitive content usually misconstrued to be favouring certain political agendas and lack of clear-cut democratic values in the curriculum framework to guide teachers on teaching democratic values. Some of the recommendations were that teachers should be protected by legal instruments to enable them to freely teach sensitive content. Teachers also need empowerment in syllabus interpretation on the teaching of democratic values to be able to effectively promote the teaching of democratic values.